Early Recognition of Septic Shock in Children - Dohna-Schwake, C.; Felderhoff-Müser, U. (Klinische Pädiatrie, 2013)
In the developed countries septic shock has a favorable outcome for the majority of previously healthy children but also in children with comorbidities if all available medical resources were used. However, septic shock remains a rare disease in children, and caregivers might not always recognize it at early stages. The resulting delay of appropriate treatment prevents lower mortality rates. The current review gives an overview of the pathophysiology of septic shock and the early clinical signs as well as new and future diagnostic approaches such as “point-of-care” laboratory tests for an early diagnosis.
Keywords: septic shock; early recognition; pathophysiology; capillary refill